Formulation, physicochemical evaluation and antimicrobial activity of green toothpaste on streptococcus mutans - Ogboji, Joel; Y. Chindo, I.; Jauro, Aliyu; Boryo, D; N. M., Lawal (International Journal of Advanced Chemistry, 2018)
Background: Toothpaste is a cosmetic product with increasing relevance and demand. However most commercial toothpaste consist of complex chemicals whose health safety remain unclear.Objectives: The present work involves the formulation, and comparative physicochemical evaluation and antimicrobial activity of green toothpaste and three commercial toothpastes (Close-Up, Oral-B and Dabur-Herbal)Methods: The green toothpaste were formulated using Tumeric (Curcuma longa), Aloe Vera (Aloe barbadensis miller), Guava (Psidium guajava), Mint (Mentha piperita), Neem (Azadirachta indica), and Lemon (Citrus lemon) as the active ingredients and comparatively evaluated for various properties like colour, taste, odor, texture, abrasivity, spreadability, cleansing ability, foaming ability, stability, homogeneity, moisture content, gritty matter and pH. The antimicrobial activity of the formula was comparatively tested on Streptococcus mutans (the major causative organism of dental caries).Results: Cold extracts of plant materials with ethanol showed a relative low (3.6% - 6.8%) percentage recovery of bioactive compounds. Physico-chemical tests revealed that the spreadability, pH, foam, gritty matter and homogeneity gave favourable results that compares well with commercial ones. The result of the antimicrobial test shows significant difference between the mean zones of inhibition of the various toothpastes.Conclusion: The results of the study agree with traditional application of the herbaceous plants and showed that the formulated toothpaste contains phytochemicals which possess antimicrobial properties and may be safer compared to toothpaste consisting of synthetic chemicals.Â